Oral habit frequency of 7-15 years old homeless children - Damayanti, Nur Widya; Musnamirwan, Iwan Ahmad; Indriyanti, Ratna (Padjadjaran Journal of Dentistry, 2014)
Introduction: Oral habit is a bad habit that causes dental changes if habit are continued for long periods of time. Oral habit included digit sucking, lip sucking or biting, nail biting, mouth breathing. The purpose of study is to know the condition of oral habits in 7-15 years old homeless children undercare of Rumah Perlindungan Anak GANK (Generasi Anti Narkotika & Kriminalitas). Methods: This study was a descriptive research by survey technique. The sample consisted of 46 children collected by total sampling. Data pertaining to the study was collected through interviews in form questionnaire and clinical examinations.Result: The result shows that 71,74% have oral habits, consisting of 18 boys (54,54 %) and 15 girls  (45,45 %), out of which 26,09% homeless children have lip sucking or biting, 21,74 % have nail biting, 17,39 % have mouth breathing and 6,52 % have thumb sucking habit. Conclusion: Oral habit frequencyvwere most performed in homeless children was lip sucking or biting.